Influence of the Vatican II Council and Its Resolutions to Formation of the Catholic Resistance in Lithuania - Jaseliūnas, Egidijus (Genocidas ir rezistencija, 2002)
The Vatican II Council (1962–1965) was the first Ecumenical Meeting where all problems regarding the religion of the modern times, and life of the Church were discussed. Having established the idea of renovation, the Council introduced new and more comprehensive conception of the Church. The conception anew considered the essence of the Church, its aims, and role in the modern world. Despite peculiar situation of Lithuania during the Soviet occupation, these trends of the development of the Catholic Church, anchoring in the life of the Church since the sixties, also became a constituent of the Lithuanian Catholic Church, and determined formation of the Catholic resistance against the Soviet authorities, the character and forms of it. The development trends of the Catholic Church established during the Council were reflected in the Catholic resistance movement already during the implementation of the liturgical reform ratified by the Soviet authorities. However, implementation of the conception of the renovated Church inevitably contradicted the position of the Soviet system regarding the Church. Therefore, to spread this conception under the totalitarian regime, it was possible only in the underground activities. Implementation of the idea of renovation became the foundation on which formed was the underground Church resisting Soviet suppressions in sixties and seventies. Moreover, a number of Council resolutions realized and transformed also made an impact on a wider range of spheres and forms of activities of the underground Church. Having established the principle of the right for religion and having raised an idea to protect this right by all means, the Council gave ideological reason for activities of all Churches persecuted. The Catholic resistance movement treated this principle as an ideological base for its activities. It can even be stated that namely this principle was the reason for the open Catholic opposition, which rose also due to the repressions perpetrated by the Soviet authorities against the more active pastoral activities of the underground Church. Setting new trends of the Church activities, the Council also encouraged formation of the Catholic periodical samizdat in the seventies. The provisions ratified on actual questions of the time in the resolutions directly affected the character and further development of this samizdat.